DINING ‘ON AND OFF’: FOOD, WELLBEING AND WECHAT USE AMONG OLDER CHINES MIGRANTS IN AUSTRALIA - Wang, Wilfred Yang; Yang, Yanan Jana (AoIR Selected Papers of Internet Research, 2020)
This study examines how WeChat, one of the most popular Chinese messenger applications installed on smartphone, facilitates the formation of an older Chinese diasporic space that is centered around the self-nurturing diet (yinshi yangsheng) cultural discourse in Australia. Media has traditionally played a crucial role in disseminating yangsheng-related information and knowledge in China (Sun 2016). However, currently literature in older Chinese people’s media consumption mainly focuses on experience and processes within China few have paid attention to surging number of older Chinese who are ageing in a transnational context. Through analysing data collected from eight focused group (12 people each) conducted at a Chinese restaurant in Brisbane, Australia, and examining OCM participants’ WeChat use,it is found that WeChat not only facilitates the formation of an older Chinese social space in Australia but the platform has acted as a self- and mutual-reliance mechanism for OCMs to negotiate and make sense of their biological change of ageing and biographic change of transnational migration.